Conflict Management between the State and the People: A Case of Power Plant in Thailand - Kesarat, Chaiya; Rinthaisong, Idsaratt (International Journal of Social Sciences and Management, 2016)
The purposes of the study were: 1) to study situation of conflict between the state and the people on the power plant project; 2) to seek causes of conflict between the state and the people; and 3) to offer guidelines to conflict management between the state and the people. A qualitative methodology was used in this study. Key informants were residents living around the project, and a semi-structured interview instrument was used to conduct in-depth interviews with 12 key informants. Results of the study revealed that the current conflicts resulted from the irrationality of the benefits that people obtained from the project, and the environmental, societal and cultural issues. Besides, the conflict in the community is caused by interference of third parties/actors. The causes of the conflict are rooted in three aspects: firstly, the structural bureaucracy; secondly, the attitude and performance of government officials; and finally, the lack of participation of the people. The guidelines to conflict management are divided into two groups: the first group is guideline for the management of within the bureaucracy; the second group is guidelines for the management of relationships between the state and the people in the area. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 214-221